TRANSFORMASI SUPERVISI ADAPTIF PADA ERA DIGITAL - Ariyadi, Ariyadi; Julaiha, Siti; Muadin, Akhmad (STKIP Pesisir Selatan, 2025)
Educational supervision in the digital era contributes to transformation with an approach that is more adaptive, flexible and based on the real needs of education. The development of educational technology and the implementation of the new curriculum make adaptive supervision a response to changes in the dynamic learning environment. This article aims to examine in more depth the forms of adaptive supervision transformation in supporting the effectiveness of improving learning quality. A qualitative method with a literature study approach is used to identify various transformations of adaptive supervision. Scientific journals, academic books, policy reports, and recent research results are the sources of research data. The analysis used was content analysis. The results showed that the transformation in adaptive supervision identified two things, namely: (a) adjusting the approach to the characteristics of teachers and the environment; and (b) utilizing digital technology to support communication, data analysis, and learning reflection. The results of this study have implications for responsibility for the challenges faced with systemic support and continuous training.